Pressure Engineering for Extending Spectral Response Range and Enhancing Photoelectric Properties of Iodine. Issue 21 (17th August 2021) - Li, Zonglun; Li, Haiyan; Liu, Nana; Du, Mingyang; Jin, Xilian; Li, Quanjun; Du, Yi; Guo, Lin; Liu, Bingbing
Abstract: Constantly exploring and improving the photoelectric properties of functional materials is of paramount importance for the development of the optoelectronics industry. Herein, a new strategy to extend the spectral response range and enhance the photoelectric properties of functional materials using high pressure is presented. In addition, the successful application of this strategy to the regulation of the photoelectric properties of 2D layered semiconductor iodine is reported. The maximum photocurrent is four orders of magnitude higher than that measured under initial pressure, with visible‐light illumination. Impressively, the light‐response range of iodine is successfully extended to the near‐infrared (1064 nm) with the application of pressure, and the photoresponse properties are also significantly enhanced with compression. These dramatically enhanced photoelectric activities are attributed to charge delocalization as well as an increased charge density in the regions between parallel molecules, which occur as a result of pressure‐induced charge transfer in the iodine molecules. These findings can be extended to guide the modification of the spectral response range and photoelectric properties of other functional materials. Abstract : Significantly increased iodine photocurrent, by almost four orders of magnitude, under visible light illumination and extension of the spectral response range to the near‐infrared band (1064 nm) for 2D layered semiconductor iodine is achieved using high pressure. These findings provide new insights into the design of novel photoelectric functional materials.